Zakat Collection System in Zakat Amil Agency (Baz) Pekanbaru City - Achmad Ghozali (MultiTech Publisher, 2024)
The collection of zakat (divine tax) is one of the main responsibilities of the zakat amil (collector). In fulfilling these responsibilities, the Pekanbaru City Regency BAZ has been successful. Therefore, this research aims to determine the growth of zakat collection in the Pekan baru City Regency BAZ during the 2010-2015 period in terms of nominal value, sources and efforts made in zakat collection. To achieve this aim, this research uses a case study. The findings show that the amount of zakat collected during the period increased significantly to a total of more than IDR 34.44 billion. This increase is far above the average that can be achieved globally. In terms of zakat sources, the sources are expanded from professional zakat to other sources, such as trade and services zakat. To support the success of zakat collection, Pekanbaru City Regency BAZ continues to strive to improve the Zakat Collection Unit (UPZ), form a marketing team, distribute marketing tools, and carry out massive zakat outreach.